Patrystyczna interpretacja Rdz 2, 7: „Pan Bóg ulepił człowieka z prochu ziemi i tchnął w jego nozdrza tchnienie życia” - Czyżewski, Bogdan (Vox Patrum, 2016)
The article aims at the presentation of the exegesis of Gen 2:7 made by some early Christian writers. Their interpretation contains three essential elements. Fathers start with pointing out the matter as a material from which God created man. Although the human body undergoes natural decomposition, it is not because of the material from which it is built, but because of its frailty due to sin. Fathers also pay attention to the soul, which has its source in what Genesis calls the breath of God. However, it did not exist before the creation of the material body, as proclaimed by Origen, but was created along with the body. The soul animates the body putting it in motion. Although man was formed from the dust of the earth by the hands of God, he should be seen as a spiritual being. Whereas the soul is created, the body has been formed and this clearly differentiates the two. Due to the greatness and grandeur of man, he cannot be reduced to animal being, as it has a rational soul that animates his body. Finally, the third thread in connection with the exegesis of the Gen 2:7 indicates the union of the body and the soul at the moment of creation. It occurred at the time when God breathed into man’s nostrils and put in some part of his grace. This does not mean, however, that the nature of God has changed into the soul of man. Not only did the first man receive the breath of God – everyone gets a second breath, the Holy Spirit, which leads to the creation of a new humanity.